2016
DOI: 10.1098/rspb.2016.1845
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding parents should invest more resources in fewer offspring

Abstract: Inbreeding increases parent–offspring relatedness and commonly reduces offspring viability, shaping selection on reproductive interactions involving relatives and associated parental investment (PI). Nevertheless, theories predicting selection for inbreeding versus inbreeding avoidance and selection for optimal PI have only been considered separately, precluding prediction of optimal PI and associated reproductive strategy given inbreeding. We unify inbreeding and PI theory, demonstrating that optimal PI incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 54 publications
(137 reference statements)
1
31
0
Order By: Relevance
“…We also found that females that were mated to related males (and thus were producing inbred offspring) laid fewer eggs than those that were mated to unrelated males (and thus producing outbred offspring). This finding is consistent with a recent theoretical model predicting that parents producing inbred offspring should produce fewer offspring and invest more resources in individual offspring (Duthie et al ., ). Additionally, we found that females producing highly inbred offspring took longer to begin egg laying after encountering the carcass.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We also found that females that were mated to related males (and thus were producing inbred offspring) laid fewer eggs than those that were mated to unrelated males (and thus producing outbred offspring). This finding is consistent with a recent theoretical model predicting that parents producing inbred offspring should produce fewer offspring and invest more resources in individual offspring (Duthie et al ., ). Additionally, we found that females producing highly inbred offspring took longer to begin egg laying after encountering the carcass.…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence that maternal care buffers against the detrimental effect of offspring inbreeding in N. vespilloides (Pilakouta et al ., ). Furthermore, the smaller clutch sizes laid by females producing inbred offspring may lead to a lower initial number of larvae hatching, which would allow females to provide more care to each larva in inbred broods as predicted by a recent theoretical model (Duthie et al ., ). Thus, nonlinear effects of inbreeding could arise if females overcompensate for the detrimental effects of moderate offspring inbreeding by providing more care, resulting in higher larval survival for moderately inbred offspring compared to outbred offspring.…”
Section: Discussionmentioning
confidence: 97%
“…It is likely that the homozygous state of loci with deleterious recessive alleles leads to a decrease in inbred offspring fitness (Charlesworth & Willis, 2009). Another hypothesis is that a female mating with a relative should increase her parental investment in the inbred offspring, therefore reducing their number (Duthie, Lee, & Reid, 2016). So far the possibility that parents decrease their investment in these broods to limit energetic expenditure in producing bad quality homozygous offspring has received little attention (Bilde, Maklakov, & Schilling, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, experimental evidence for the adaptive significance of variation in egg size across different conditions is limited, possibly because experimental conditions do not adequately mimic the complexity of natural environments. Other biotic factors that strongly select for large or small differential offspring size include food quality (e.g., Brody and Lawlor, 1984;Braby, 1994), competition (e.g., Parker and Begon, 1986), inbreeding (e.g., Duthie et al, 2016), limited dispersal (e.g., Kuijper and Johnstone, 2012) and predation (e.g., Kerfoot, 1974;Ernsting and Isaaks, 1997) (see also Table 2 in Rollinson and Rowe, 2016). In particular, increased competition generally selects for larger offspring size, while sizedependent predation may select for either smaller or larger offspring.…”
Section: Environmental Factors Influencing Offspring Size Within Speciesmentioning
confidence: 99%